Attitudes toward Abortion among the Muslim Minority and Non-Muslim Majority in Cross-National Perspective: Can Religiosity Explain the Differences?. (13th June 2017) - Carol, Sarah; Milewski, Nadja
Abstract: What are the attitudes of Europeans with or without immigrant backgrounds toward abortion? Who opposes or approves of the practice? To investigate these questions, we draw on the EURISLAM survey, which gathered data on nonmigrants and non-Muslims (majority) in Belgium, Britain, France, Germany, and Switzerland as well as on Muslim minorities of immigrant origin (from Morocco, Turkey, Pakistan, and the former Yugoslavia) who are resident in these European countries. Taking assimilation theory as our point of departure, we hypothesize that the societal climate towards abortion in the country of residence explains the attitudes of the Muslim minority. Regression analyses reveal that minorities partly adopt the country-of-residence attitudes: French residents are the most accepting of abortion, while German residents are the least. We also examine whether the level of religiosity explains denominational differences in attitudes toward abortion. Within and between countries, there remain attitudinal differences between Muslims, Christians, and atheists, and these cannot be entirely explained. These differences are likely to persist across immigrant generations.